AB0294 Analysis of Prognosis Factors for Functional Disability in a Japanese Cohort for Rheumatoid Arthritis. (9th June 2015) - Furu, M.; Hashimoto, M.; Fujii, T.; Ito, H.; Ishikawa, M.; Terao, C.; Yamakawa, N.; Yamamoto, W.; Yoshitomi, H.; Matsuda, S.; Mimori, T.
Abstract : Background: Functional disability is one of most important factor which should be improved in treatment with rheumatoid arthritis (RA). Objectives: The aim of this study is to explain prognosis factors for functional disability in RA. Methods: We chose the 301 of consecutive RA patients, with both 2012 and 2013 RA survey in our observational Japanese cohort, and assessed clinical variables including age, duration, stage, class, ACPA, RF, DAS28, ΔDAS28 (DAS28 2013 minus DAS28 2012 ), HAQ, ΔHAQ (HAQ 2013 minus HAQ 2012 ), modified Total Sharp score (mTSS), and DMARDs. We search prognosis factor for ΔHAQ by multivariate analyses. Results: Mean age was 62.1 years old. Mean disease duration was 14.5 years. MTX was used 71.1% of patients. Biologics was used 32.6% of patients. Mean follow-up time was 414.5 days. In linear regression analysis, predictors for increasing ΔHAQ were HAQ 2012 (t=-2.90, p <0.01), no-usage of MTX (t=2.28, p=0.02), no-usage of biologics (t=2.08, p=0.03), and age (t=2.23, p=0.02)(Table1 ). In logistic regression analysis, prognosis factors for ΔHAQ >0 were no-usage of MTX (OR=1.98, p=0.02) and no-usage of biologics (OR=2.63, p<0.01)(Table2 ). There was no correlation between ΔHAQ and DAS28 2012 . There was statistically correlation between ΔHAQ and ΔDAS28 (r=0.43, p<0.01). Conclusions: Our study demonstrated that prognosis factors for functional disability in RA were no-usage of both MTX and biologics. Disclosure of Interest: M. Furu Grant/research support from: Astellas Pharma Inc., Pfizer Japan Inc., Employee of: Mitsubishi Tanabe Pharma Co., Bristol-Myers K.K., Chugai Pharmaceutical Co., Ltd., AbbVie GK., Eisai Co., Ltd., M. Hashimoto Grant/research support from: Astellas Pharma Inc., Pfizer Japan Inc., Employee of: Mitsubishi Tanabe Pharma Co., Bristol-Myers K.K., Chugai Pharmaceutical Co., Ltd., AbbVie GK., Eisai Co., Ltd., T. Fujii Grant/research support from: Takeda Pharmaceutical Co., Santen Pharmaceutical Co., Ltd., Astellas Pharma Inc., Asahi Kasei Pharma Corporation, and Daiichi Sankyo Co., Ltd, Employee of: Mitsubishi Tanabe Pharma Co., Bristol-Myers K.K., Chugai Pharmaceutical Co., Ltd., AbbVie GK., Eisai Co., Ltd., H. Ito Grant/research support from: Takeda, Daiichi-Sankyo, Chugai, Tanabe-Mitsubishi, Bristol-Meyers, M. Ishikawa: None declared, C. Terao: None declared, N. Yamakawa: None declared, W. Yamamoto: None declared, H. Yoshitomi: None declared, S. Matsuda Grant/research support from: Zimmer, Biomet, Smith and Nephew, Kyocera, Consultant for: Biomet, Kyocera, Speakers bureau: Zimmer, T. Mimori Grant/research support from: Asahi Kasei Pharma Corporation, Astellas Pharma Inc., Bristol-Myers Squibb K.K., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Corporation, Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., and Takeda Pharmaceutical Co., Ltd., Speakers bureau: AbbVie GK., Bristol-Myers Squibb K.K., Chugai Pharmaceutical Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Corporation, Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd